Implementation of a Camera-Based Inspection System for Measuring the Diameter of 3D Printed Filaments Made from LDPE Water Bottle Caps - Sunarya, Adhitya Sumardi; Candra, Wahyu Adhie; Lestari, Miranti; Taqi, Khoutal (Jurnal Edukasi Elektro, 2025)
Advances in additive manufacturing technology are driving the need for high-quality, affordable, and sustainable filaments. In Indonesia, the demand for filaments and extruders is largely met through imports, prompting researchers to innovate and develop filament extrusion machines, including those at the Politeknik Manufaktur Bandung, which has developed a filament extrusion machine equipped with a camera-based inspection and control system to produce high-quality filaments from LDPE gallon cap waste. This system integrates a digital microscope camera and a microcontroller to monitor the diameter of the extruded filament and correct the diameter by controlling the speed of the pull motor to stabilize the diameter in real-time. Image processing uses a color-based edge detection algorithm, and camera calibration results show a precision of 0,009 mm/pixel. Diameter data is sent to the Arduino Mega, which then uses the L298N driver to control motor speed via the Sliding Mode Control (SMC) method. Test results show that at 15 RPM, the average filament diameter is 1,77 mm with an error of 1,14%, while at 20 RPM it becomes 1,56 mm with a larger error of 10,86%, compared to the standard commercial filament size of 1,75mm. SMC control also demonstrated better performance than PID in terms of system accuracy in reaching the set point. This system could serve as an economic and ecological solution for local recycled filament production, reducing dependence on imported products.